Counterorienting the war on terror: Arab hip hop and diasporic resistance. Issue 2 (June 2017) - Drury, Meghan
Abstract: This article discusses Arab hip hop as a transnational genre produced out of a state of upheaval, resisting political and economic oppression. One impact of the 9/11 attacks was to make Arabs and Muslims increasingly visible in the US public, reflecting what Nadine Naber has termed a "diaspora of empire." Arab hip hop points to a unique nexus reflecting the web of cultural and economic realities in the 21st century. I argue that sampling practices, sonic layering, and linguistic play in Arab hip hop allow artists to enact geographic and temporal flexibility and facilitate a diasporic resistance that challenges public fear and repressive state discourse.